2015
DOI: 10.1088/0953-8984/27/43/435002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a reversible shear transformation on plastic deformation of an amorphous solid

Abstract: Molecular dynamics simulations are performed to investigate the plastic response of a model glass to a local shear transformation in a quiescent system. The deformation of the material is induced by a spherical inclusion that is gradually strained into an ellipsoid of the same volume and then reverted back into the sphere. We show that the number of cage-breaking events increases with increasing strain amplitude of the shear transformation. The results of numerical simulations indicate that the density of cage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The spatial correlations of the local strain field clearly showed the fourfold patterns, characteristic of Eshelby inclusions, that are present even in a quiescent system where their orientation is isotropic, thus producing zero global strain [20]. In turn, a local reversible shear transformation in a quiescent glass can trigger irreversible cage jumps whose density is large when the system dynamics is weakly damped or the shear transformation is slow [21,22]. More recently, a sharp transition from affine to nonaffine displacements of particles was identified in colloidal glasses under variable-amplitude oscillatory shear [6,7].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The spatial correlations of the local strain field clearly showed the fourfold patterns, characteristic of Eshelby inclusions, that are present even in a quiescent system where their orientation is isotropic, thus producing zero global strain [20]. In turn, a local reversible shear transformation in a quiescent glass can trigger irreversible cage jumps whose density is large when the system dynamics is weakly damped or the shear transformation is slow [21,22]. More recently, a sharp transition from affine to nonaffine displacements of particles was identified in colloidal glasses under variable-amplitude oscillatory shear [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…In turn, a local reversible shear transformation in a quiescent glass can trigger irreversible cage jumps whose density is large when the system dynamics is weakly damped or the shear transformation is slow [21,22]. More recently, a sharp transition from affine to nonaffine displacements of particles was identified in colloidal glasses under variable-amplitude oscillatory shear [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, during cyclic shear near the yield strain, a cluster of atoms with large reversible nonaffine displacements induces a long-range, time-dependent elastic field that in turn might trigger secondary structural rearrangements. This situation was considered separately in recent studies [31,32], where it was found that a local reversible shear transformation in a quiescent system induces irreversible cage jumps, and their density is larger in the cases of weaker damping or slower shear transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a local plastic event in sheared amorphous solids induces long-range deformation that in turn might trigger secondary events and give rise to avalanches [12]. In related studies, it was shown that a local reversible shear transformation in a quiescent system results in cage jumps (discrete events where particles escape from cages of their neighbors) whose density is larger in the cases of weakly damped dynamics or slow shear transformation [13,14].…”
Section: Introductionmentioning
confidence: 99%